2017
DOI: 10.20959/wjpps20179-9806
|View full text |Cite
|
Sign up to set email alerts
|

STABILITY INDICATING RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR ESTIMATION OF EMPAGLIFLOZIN AND METFORMIN HCl

Abstract: One simple, specific, accurate, precise and reproducible and robust respectively. The % recoveries of Empagliflozin and Metformin HCl were found to be 99.60% -100.48% and 100.15% -100.23% respectively. Method was statistically validated for accuracy, precision, specificity, LOD, LOQ and robustness according to ICH guidelines.Developed method was found to be new, accurate, precise and rapid for simultaneous estimation of for Empagliflozin and Metformin HCl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…[6] Several HPLC methods have been developed for the determination of REM with other drugs such as metformin, teneligliptin hydrobromide hydrate, and vildagliptin. [7][8][9][10] It has been reported that a stability-indicating high-performance thin-layer chromatography approach for REM estimation in tablet formulation has been developed and validated. Studies on forced degradation conducted here reveal that the drug is extremely susceptible to conditions including acid, base, and oxidative stress.…”
Section: Original Articlementioning
confidence: 99%
“…[6] Several HPLC methods have been developed for the determination of REM with other drugs such as metformin, teneligliptin hydrobromide hydrate, and vildagliptin. [7][8][9][10] It has been reported that a stability-indicating high-performance thin-layer chromatography approach for REM estimation in tablet formulation has been developed and validated. Studies on forced degradation conducted here reveal that the drug is extremely susceptible to conditions including acid, base, and oxidative stress.…”
Section: Original Articlementioning
confidence: 99%
“…Various approaches were published in the literature for the simultaneous measurement of CAN and MET utilizing spectrophotometric [13][14][15] and high-performance liquid chromatographic (HPLC) [16][17][18][19][20][21] methods. While, EMP and MET were investigated using spectrophotometric [22][23][24][25][26][27] and chromatographic [20,21,[28][29][30][31][32][33][34][35] methods in pure and pharmaceutical form. Few published researches have discussed the simultaneous determination of the studied drugs with MEL [36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Literature review showed that limited methods of analysis were established for simultaneous determination of the triple combination such as HPLC [ 6 8 ], HPTLC[ 6 , 9 ], UPLC [ 10 ] and spectrophotometry [ 11 ],whereas, for their binary combinations, HPLC [ 12 14 ], HPTLC [ 15 – 17 ], UPLC [ 17 ], voltammetric method [ 18 ] and spectrophotometric methods were reported [ 19 – 21 ].…”
Section: Introductionmentioning
confidence: 99%